soybean sprout cultivator - LEE, SEUNG KYU (2017)
Disclosed is a bean sprout cultivator for cultivating bean sprouts by applying ultrasonic wave spray and maintaining cleanness. The bean sprout cultivator comprises: upper and lower cases; an ultrasonic wave watering device installed in the upper and lower cases and spraying stored water into the upper and lower cases through ultrasonic wave vibrator; and a tray which is fixed at fixed height in the upper and lower cases, which has a plurality of protruding drainage holes to maintain the fixed water level on the bottom surface and in which beans are germinated and grown. 콩나물 재배기가 개시된다. 본 발명은 초음파 분무를 적용하여 콩나물을 재배하는 동시에 청결을 유지할 수 있는 구조를 갖는 콩나물 재배기에 관한 것이다. 본 발명에 의한 콩나물 재배기는 상하부 케이스; 상기 상하부 케이스 내부에 설치되어 저장된 물을 초음파 진동자를 사용하여 상기 상하부 케이스 내부로 분무하는 초음파 관수기; 및 상기 상하부 케이스 내부에 일정높이로 고정되고, 바닥면에 일정 수위를 유지하도록 돌출된 복수개의 돌출배수구가 형성되어, 콩이 발아되고 생육되는 채반;을 포함한다.